Contribution of transference to the psychiatric nursing process - Murille Badin; Vanessa Pellegrino Toledo; Ana Paula Rigon Francischetti Garcia
ABSTRACT Objective: to describe the contribution of the concept of transference to the application of the nursing process in the care of patients with psychical suffering. Method: Theoretical study, structured from the following question: Is it possible to develop the nursing process in the care of patients with psychical suffering by using transference? Result: The patient is considered as a subject of the unconscious and has a demand he/she is unaware of. Discussion: The transference guides the nursing process and favors the elaboration of what has no meaning in the symptom. Final considerations: As an implication for practice, the nursing process will articulate the transference function through the nursing diagnosis, which will promote the capture of subsidies for the planning and implementation of care, in which the purpose will be the symbolization of the symptom. To highlight speech as a means to therapeutic relation will offer the patients the condition to dictate the pace of articulation between their signifiers, which will dynamically temporalize the process.